Profiling of Seawater Bacterial Diversity in Tanjung Mas Port Using 16S rRNA eDNA Metabarcoding and Next-Generation Sequencing (NGS) - Anggoro, Naufal Sebastian; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto; Wijanarka, Wijanarka; Zainuri, Muhammad; Hadibarata, Tony (Marine Science Department Diponegoro University, 2024)
Tanjung Emas Port is the entry and exit point for trade commodities, both regional and international filled with many ships. This condition makes biofouling a very massive process in that place by various types of marine bacteria. The initial formation of a biofilm is relevant to bacterial diversity, colonization and adhesion. The objective of the study was assessing bacterial diversity in relation to with biofouling within Tanjung Mas Port Semarang, by using 16S rRNA eDNA metabarcoding Next-Generation Sequencing (NGS). Seawater samples from aquatic sites of Tanjung Mas harbor was used for DNA extraction and amplification of the 16S rRNA V-3-V4 hypervariable region, followed by sequencing and library construction of eDNA Metabarcoding. Sequence processing and analysis was performed in QIIME 2 and RStudio using DADA2 for advanced sequencing processing and Phyloseq. The results of this research showed that bacteria is the predominant taxon constituting 100% of the community. The taxon consists of Proteobacteria (49.38%), Bacteroidota (8.67%), and Firmicutes (8.88%). Alphaproteobacteria (20.92%) and Gammaproteobacteria (12.39%) dominate at the Class level, emphasizing their versatility and ecological influence. At the Order and Family levels reveals the prevalence of Rhodobacterales (10.04%), Chitinophagales (2.53%), Rhizobiales (3.61%), Rhodobacteraceae (5.67%), Saprospiraceae (3.63%), and Rhizobiaceae (2.15%). It was found that the unculturable taxa dominance in Tanjung Mas Port was 44.66%. These taxonomic entities contribute significantly to the taxonomic and functional diversity of the microbial community, influencing nutrient cycling, organic matter degradation, ecosystem stability and biofilm formation.